2022
DOI: 10.1101/2022.06.15.496347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A loss of crAssphage stability in the human gut virome is associated with obesity and metabolic syndrome

Abstract: Viral metagenomics studies of the human gut microbiota unravel differences in phage populations between healthy and disease, stimulating interest in the role that phages play in bacterial ecosystem regulation. CrAssphages are not only the most abundant viruses but also are a common component of the gut phageome across human populations. However, the role of crAssphages in obesity (O) and obesity with metabolic syndrome (OMS) remains largely unknown. Therefore, we explored the role that crAssphages have on both… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…According to previous studies, the intestinal microbiome, especially the abundance of Bacteroides, is affected by intestinal diseases, such as IBS, Crohn's disease, and CRC (Wang et al, 2021;Zafar and Saier, 2021). Moreover, a recent study reported that crAssphage subfamilies showed different stability in the human phageome dependent on the abundance of Bacteroidales in the gut of people suffering from obesity and metabolic syndrome (Cervantes-Echeverria et al, 2022), suggesting that the association between human diseases and crAssphage prevalence may be dependent on the abudance of host species of each crAssphage subfamily. However, those crAssphage-targeting primer/probe combinations cannot discriminate its subfamilies for detection and monitoring at this time.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the intestinal microbiome, especially the abundance of Bacteroides, is affected by intestinal diseases, such as IBS, Crohn's disease, and CRC (Wang et al, 2021;Zafar and Saier, 2021). Moreover, a recent study reported that crAssphage subfamilies showed different stability in the human phageome dependent on the abundance of Bacteroidales in the gut of people suffering from obesity and metabolic syndrome (Cervantes-Echeverria et al, 2022), suggesting that the association between human diseases and crAssphage prevalence may be dependent on the abudance of host species of each crAssphage subfamily. However, those crAssphage-targeting primer/probe combinations cannot discriminate its subfamilies for detection and monitoring at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whole-virome analysis of inflammatory bowel disease (IBD) and ulcerative colitis (UC) datasets shows IBD-specific alterations in the gut virome, specifically a loss of crAss-like phages and Microviridae , identifying crAss-like phages as critical components of the core virome in healthy individuals [ 16 ]. Another study reporting loss of phageome stability in disease found reduced abundance and diversity in children with obesity and obesity-related metabolic syndrome [ 15 ]. The fact that a virulent crAssphage core represents a healthy microbiome at equilibrium and that virome dysbiosis can be overcome by FMT highlights the importance of considering the viral portion of a patient’s metagenome when considering FMT therapy [ 38 ].…”
Section: Metagenomics Diversity and Ecology Of Crassviralesmentioning
confidence: 99%
“…As no detrimental associations between human health and the presence of crAssphage have yet been found, it has been deemed a benign entity in the gut microbiome [ 11 , 12 ]. A beneficial role in the human gut has been suggested by observations of depleted crAss-like phage populations in patients with inflammatory bowel disease, and a destabilisation of p-crAssphage is linked to obesity and metabolic syndrome [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%